When nomenclature and morphology unravel an enigma: the true identity of Ouratea crassinervia (Ochnaceae) - John Teixeira, Luíza; Araújo, Michelly de Deus Felipe; Deccache, Lara Serpa Jaegge; Fraga, Claudio Nicoletti de (Plant ecology and evolution, 2025)
Background and aims – The taxonomy of any group is the sum of publications scattered throughout the literature added to the application of the International Code of Nomenclature for algae, fungi, and plants. A significant part of being a group specialist is the ability to apply a Linnaean binomial correctly and resolve conflicts in the light of the Code. Over the years, Ouratea crassinervia has been misidentified as O. verticillata , a species restricted to southern Rio de Janeiro and northern São Paulo states. Additionally, the name O. crassinervia began to be applied as an accepted name in Central America, with O. costaricensis and O. curvata mistakenly as its synonyms. On the other hand, there was no mention of O. crassinervia in species lists or monographs for the Brazilian Flora until 2020, when it appeared as a synonym for O. curvata , repeating another misinterpretation. Material and methods – From 2021 to 2024, we conducted fieldwork in northern Rio de Janeiro. Furthermore, specimens for all “dracenoid” species were studied in several Brazilian herbaria, and some were examined online. The morphological data of the description were obtained through the analysis of both living and dried specimens observed in the field and the herbarium. The assessment of O. crassinervia conservation status was according to the IUCN Red List Categories and Criteria. Key results and conclusion – Ouratea crassinervia is endemic to the low Atlantic Forest in the northeastern part of Rio de Janeiro, Brazil, and limited to the south by the Guanabara Bay. Morphologically, O. crassinervia is similar to O. cauliflora , O. dorata , and O. verticillata from the Brazilian Atlantic Forest, O. ramiflora from the Amazon, and O. costaricensis and O. theophrasta from Central America, due to the “dracenoid” habit, but can be easily distinguished by its terminal inflorescence and larger flowers. This work provides a discussion of the architectural model and the inflorescences for each species in the group and an emended key for the “dracenoid” Ouratea species.